Peculiarities of Socio-economic Support of Federal Subjects of Russia - Zalivanskiy, Boris V.; Samokhvalova, Elena V.; Novikova, Lidia P.; Taranova, Irina V.; Anopchenko, Tatyana U.; Glushko, Anatoly J. (International Journal of Economics and Financial Issues, 2016)
Economic support of the population in the Russian Federation suggests ways to interact with the help of which the specialists of social work have an impact on material and moral, national, family and other social interests and needs of subjects of social work. These methods play a leading role in the process of impact of social work on the individual and social groups. Socio-economic methods are applied in the form of natural and financial aid, establish benefits and lump sum benefits and compensation, patronage and consumer services, moral incentives and sanctions and so on. The correct application of economic methods in the technology of social work is assessed by their effectiveness, i.e. achieving the greatest social impact for clients and society with optimal expenses. Economic methods of support for population and social work occupy a Central place in the mechanism of social support; they affect the main aspects of the system of social protection, on the one hand, encouraging the individual to self-realization of its potential opportunities and self-sufficiency, providing individual, family, group specific socio-economic support in a crisis situation. Keywords: economic support, economic situation, economic methods, socio-economics JEL Classifications: H50, H53, L81, L84, M31